PENGARUH KEKUATAN CAMPURAN ASPAL PANAS LASTON TIPE IV SNI 03-1737-1989 AKIBAT PENAMBAHAN SERAT ECENG GONDOK - Widyastuti Dwi Pratiwi; Sugeng Dwi Hartantyo (Litbang Pemas - Universitas Islam Lamongan, 2019)
Road is the land transportation that has an important role to facilitate all human activities, while tropical climate condition such as in Indonesia causes damage to the road. To engineer the hot asphalt mixture in order to have high durability, especially in Type IV Asphalt Concrete, it needs additional material to it, such as roadcel-50 cellulose fiber. However, it is considered not economical because the cellulose fiber made by the factory is quite expensive. Therefore, the researcher wants to replace it with water hyacinth fiber obtained from the river in the area of Dinoyo, Deket District, Lamongan Regency that not yet widely utilized. The mixing process of Type IV Asphalt Concrete with water hyacinth additional material starts from preparing the tools and materials, making the simple water hyacinth fiber, examining the stacking materials (including examining the coarse aggregate, fine aggregate, and asphalt), making Job Mix Formula of Tipe IV Asphalt Concerete and making the test objects of Type IV Asphalt Concerete. From the results of Marshall Test, the researcher analyzed the results with regression analysis. The results obtain 6 characteristics that meet the standard with water hyacinth mixing, those are marshall stability of voids mineral aggregate, voids in mix, density, flow, and marshall quotient with the addition of an ideal water hyacinth fiber variation of 0,02% - 0,06%. While on the voids filled with asphalt test on Marshall Test obtained the result that does not meet the requirements, but it does not matter to the whole result.